FAKTOR - FAKTOR YANG MEMPENGARUHI PENYALURAN KREDIT PADA BPR DIKOTA BATAM - Fernandes, Edrian; Hikmah, Hikmah (LPPM Universitas Putera Batam, 2021)
The amount of credit granted is determined by various factors including Non Performing Loans (NPL), Operating Costs on Operating Income (BOPO), and Loan to Deposit Ratio (LDR). The purpose of this research is to find out how far the relationship between NPL, BOPO, and LDR to the amount of credit disbursement at BPR Banks in Batam City. This research was conducted at BPR banks in Batam city for 2017-2019 period with 28 of population banks and the total of samples using purposive sampling technique. Data collection method used is non-participant observation method with data analysis technique used is multiple linear regression. The results show that the NPL and BOPO variables have a significant negative effect on credit distribution, while the LDR variable has a significant positive effect on credit distribution